First record of the genus Trypetisoma Malloch, 1924 (Diptera, Lauxaniidae) for China with nine species - Li, Wenliang; Qi, Ling; Yang, Ding (Zootaxa, 2019)
Eight species of Trypetisoma Malloch, 1924 from Southwest China are described as new to science: T. (Trypaneoides) endosclerita sp. nov., T. (Tn.) jinpingensis sp. nov., T. (Tn.) menglunensis sp. nov., T. (Tn.) semicircularis sp. nov., T. (Tn.) trimaculata sp. nov., T. (Tn.) triprocessa sp. nov., T. (Tn.) xii sp. nov., T. (Trypetisoma) spinosa sp. nov., and T. (Tn.) fenestrata (de Meijere, 1910) is recorded for China for the first time. These species represent the first records for the subgenus Trypetisoma for the Oriental region. A key to the subgenera and species of genus Trypetisoma in the Oriental region is presented.